Potencial antibacteriano e tripanocida da proteína recombinante rCV2736 de Chromobacterium violaceum produzida em células de Pichia pastoris - Medeiros, Suelen Carneiro de (2018)
The indiscriminate use of antimicrobials has led to the emergence of microorganisms presenting resistance to antibiotics. The study of genes from various organisms has become an alternative in the development of new drugs. Chromobacterium violaceum is a Gram-negative bacterium, presenting ORFs (Open Reading Frame) that code for proteins of biotechnological use. rCV2736 is a recombinant Chitinase-like, produced in Pichia pastoris KM71H, which presented low chitinolytic activity, but with antibacterial activity. This work aimed to evaluate the potential of the recombinant protein of C. violaceum ATCC 12472, rCV2736, as an antimicrobial, as well as to determine its mechanism of action. For this, the recombinant protein was purified by hydrophobic chromatography and characterized by N-terminal sequencing, deglicosylation, mass spectrometry, chitinase activity and peptidoglycan hydrolase. Biological activity was evaluated by determining the minimum inhibitory concentration (MIC) and Minimum bactericidal concentration (MBC) by microdilution in broth, effect of exposure time on bacterial viability, effect of pH change on antimicrobial activity, modulating effect on antimicrobial activity of clinical use, antibiofilm activity, antiparasitic activity, hemotoxicity and simulation by molecular docking. rCV2736 showed 3 isoforms after purification. The Nterminal sequence of the protein corresponding to the 42 kDa band presented 33 amino acids, among them residues added by the expression vector. Bands with apparent molecular weights of 35,682 Da and 34,988 Da were visualized due to deglicosylation by the enzyme Nglycosidase F. Mass spectrometry revealed peptides corresponding to the C and N-terminal portion, and O and N-glycosylations. Chitinase activity increased with longer incubation time (24 h) with colloidal chitin (137,5 U). Evaluating the presence of NaCl in the sample, there was no difference between the concentrations tested. The interaction with Ba2+, Ni2+ and Fe3+ caused a decrease in relative activity above 50%. In the peptidoglycan hydrolase activity, bands related to cell lysis with apparent molecular weight relative to rCV2736 were visualized. rCV2736 inhibited the growth of all strains tested, being bactericidal for Pseudomonas aeruginosa ATCC 9027 and Klebsiella pneumonia ATCC 10031 (365 μg/ml). This same concentration prevented the growth of these strains after 4 h and 8 h, respectively. Increasing the pH of the culture medium reduced the antibacterial potential of rCV2736 for the above bacteria. The synergistic effect was observed for combinations with ceftazidime, tetracycline and amikacin. rCV2736 was able to inhibit the formation of P. aeruginosa and K. pneumoniae biofilms at concentrations above 182.5 μg/mL, but a reduction in the number of CFU/mL was observed for the concentrations used on the biofilm formed. rCV2736 showed IC50 of 1089 μg/mL in the assays using epimastigotes, and 118.3 μg/mL for trypomastigotes. rCV2736 did not present haemotoxic effects. In the molecular docking simulations, it was possible to observe that the two ligands [(GlicNac)4 and (GlcNAc-MurNAc)2] interacted favorably in the predicted catalytic cleft, where interaction between the residue responsible for catalysis (Glu110) and oxygen atom of the glycosidic bond. Therefore, rCV2736 can be considered as a molecule with antibacterial and antiparasitic potential, where its possible mechanism of antibacterial action can be explained by the enzymatic effect on the peptidoglycan molecule.